Investigation of ozone synthesis in the negative pulsed corona discharge in oxygen at the combined supply voltage - Golota, V.I.; Kadolin, B.B.; Paschenko, I.A. (Вопросы атомной науки и техники, 2021)
The influence of combined supply voltage parameters (bias voltage and voltage pulse amplitude) on efficiency of ozone synthesis in the negative pulsed corona discharge in oxygen was obtained. Pulse overvoltage led to intensification of discharge processes. Bias voltage applied during the discharge channel relaxation essentially increased the efficiency of ozone synthesis. It was established that the “optimal” bias voltage which provides maximum ozone generation doesn’t depend on voltage pulse amplitude, but depends on input oxygen concentration and generated ozone concentration.